EVALUATION OF ILLUMINATION LEVEL AT LIBRARY OF SRIWIJAYA UNIVERSITY - Desheila Andarini; Ani Nidia Listianti (Journal of Industrial Hygiene and Occupational Health, 2017)
Library is one of the workplaces that most of its activities rely heavily on the eyes. Good lighting in the library room will improve comfort for work both for employees and visitors. Libraries in Sriwijaya University is a very important facility for the academic community to achieve the vision of Sriwijaya University in facing global challenges, where the library is actually a place for the source of all information, written or digitally. Therefore a library requires an adequate illumination level to support the activities of its academic community to stay active in working. Methods: Evaluating the illumination level in the libraries at Sriwijaya University by measuring and comparing the results of these measurements to the standards / requirements of Kepmenkes No. 1405/Menkes/SK/XI/2002.Results: From a total of 16 libraries measured both in Indralaya and Palembang campus, it was known that illumination levels were in the range of 100-1000 lux, on the other words, some libraries at Sriwijaya University still has unstandard illumination level, either lower or higher. Conclusion: Illumination level of libraries in Sriwijaya University does not fully meet the standard that it needs to be improved to prevent the occurrence of occupational diseases caused by poor or strong lighting. Keywords: Lighting, Illumination, Libraries